(untitled) (World Science, 2018)
Political changes, occuring in any country, are directly related to the media, which, in turn, is responsible for the reliability of the disseminated information. Any text or article requires an appropriate heading. Publicistic headings, in comparison with artistic ones, are more informative and diverse, and their author should consider many factors, affecting them. A good heading should reveal the essence of the text as much as possible, and it should arouse a reader’s interest as well. The paper also deals with the peculiarities of a newspaper text and a newspaper heading, which should be analyzed for a critical approach to the study of the researched object.